Influence of Plant Growth Regulators on In vitro Morphogenesis in Plumbago Zeylanica Linn. - Tripathi, M. K.; Tiwari, G.; Tiwari, Sushma; Tripathi, Niraj; Sharma, Mohini; Bhargav, Shashank; Patidar, S. L.; Tiwari, Sharad (Research Aspects in Biological Science Vol. 7, 2022)
The Present investigation was aimed to recognize the most responding explants, plant growth regulators and calculate their optimal concentrations and other physical aspects unveiling in vitro morphogenesis in higher rates via culturing nodal sections and leaf discs explants. Leaf disc and nodal section explants of Plumbago zeylanica were inoculated on basal media amended with diverse concentrations and combinations of different auxins and cytokinins as alone as well as in amalgamations. For inoculated nodal section, nutrient medium MS2N.5B (MS+2. 0 mgl-1 NAA+ 0. 5mgl- 1BA) evidenced appropriate for higher degree of callus initiation (91.69%), whereas culture medium MS2B (MS+2.0 mg l-1 BA) displayed higher shoot proliferating competence (84.14%). While, nutrient medium MS2B.5N (MS+2.0 mg l-1 BA+0.5 mgl-1NAA) formed shoot(s) in higher numbers (11.12) along with of bigger length (7.11 cm). For cultured leaf disc, inoculation medium MS2N (MS+ 2.0 mgl-1NAA) induced callus in higher percentage (91.12%), nevertheless greater morphogenic calli formation (45.58%) and plantlets regeneration were attained on culture medium MSN.5Td (MS+1.0mgl-1NAA + 0.5 mgl-1 TDZ). In current investigation, MS medium amended with either IBA or NAA at the concentration of 0.1 mg l-1 was proved to be optimal for inducing higher in vitro rooting response i.e., root proliferation, number(s) of roots and root length. Regenerants were established efficaciously under the field conditions after hardening with normal phenotypic characters.